Los of vas geskryf: die leksikograaf, die spelreëls en die taalwerklikheid - Botha, W.F. (Lexikos, 1992)
Word Group and Complex: The Lexicographer, the Spelling Rules and the Language Reality In the lexicon of Afrikaans there are lexical items that can occur as a word group and as a complex without a difference in meaning, e.g. rooi wyn (red wine) and rooiwyn. In some instances conflict exists between the spelling rules concerning this phenomenon and the language reality. The article deals with the treatment of the conflict by Afrikaans descriptive dictionaries. The lexicographic treatment of the conflict between spelling rules and language reality is determined by the type of dictionary involved. The inclusive dictionary is descriptive by nature and should give an honest and complete account of the language reality. The desk dictionary is prescriptive by nature and is concerned with the correct use of language as determined by, for instance, spelling rules. The 1991 edition of the Afrikaanse Woordelys en Spelreëls narrowed the gap between spelling rules and language reality and simplified the task of the lexicographer considerably. Suggestions are made for alternative treatments and the improvement of the existing treatment of lexical items occurring as word groups and complexes.